Business communication : role and impact of verbs, nouns, adjectives and adverbs / Fatimah Dinna Mohd. Din - Mohd. Din, Fatimah Dinna (Academy of Language Studies & UPENA, 2005)
This paper explains the role and impact of content words in their noun, verb, adjective and adverb linguistic forms in line with business communication principles of objectivity, conciseness, consideration, courtesy, concreteness, clarity, correctness and coherence. This paper also discusses an error analysis of university business ESL students' letters, reports and summary writing. There was evidence of verb, noun, adjective and adverb errors that violated business communication principles of correctness, clarity and coherence. This paper recommends the use of business communication principles as a criterion for improving and evaluating the quality of verbs, nouns, adjectives and adverbs in documents required by organisations. Additionally, the paper recommends tasks that involve simultaneous transformation of information and linguistic transformation.